Functional crop types are more important than diversity for the productivity, profit and risk of crop sequences in the inner Argentinean Pampas - Videla Mensegue, Horacio Rogelio (2021)
CONTEXT: Over the last 250 years, many natural ecosystems in South America, including the Inner Pampas of Argentina, evolved into extremely simplified agroecosystems. In the last 25 years, simplified soybean-based crop sequences have become widespread. Putative drivers of the wide adoption of this system include high soybean grain price, simplified agronomic management and low cost, but comparison of production, profit and risk in current and alternative crop sequences are lacking. OBJECTIVE: Our aim was to compare the production, profit, and risk of seven crop sequences varying in their diversity, cropping intensity and the proportion of functional crop types. METHODS: We modelled seven typical or feasible crop sequences for two locations with different rainfall and soil water holding capacity for a 50-yr period. Crop sequences included wheat (W) or fallow during winter and soybean (S) or maize (M) as single and double crops during summer, and were characterized with indexes of agrobiodiversity (ABDI, from 0.33 to 1.00), cropping intensity (from 0.40 to 0.83) and soybean proportion (SP, from 0 to 1.00). RESULTS AND CONCLUSIONS: W/M-M had the highest and S-S the lowest yield in both locations. The high yielding crop sequences had a lower stability of grain yield that those with a high proportion of soybean (S-S and W/S-S). Yield stability and CVaR (conditional value-at-risk) for gross margin and gross margin ratio were unrelated with ABDI. The prevalent, least diverse soybean monoculture (S-S) had the lowest cost and medium profit-risk metrics. Increasing the proportion of maize contributed to higher gross margin and gross margin ratio with a lower risk in some crop sequences. Crop sequences with high proportion of soybean (S-S and W/S-S) had low mean cost with a close to average CVaR. However, these were not the sequences with the highest gross margin or gross margin ratio. Our results demonstrated that functional crop types (cereal and legumes) were more important than diversity and cropping intensity for the profit and risk of crop sequences in the Inner Argentinean Pampas. SIGNIFICANCE: Economic risk-benefit analysis of crop sequences is necessary but not sufficient to understanding the drivers of grower's choices, which are greatly influenced by context regarding policies for grower support, taxes, and land ownership.